RAQAMLI TURIZM – ZAMONAVIY IQTISODIYOTNING YANGI YO‘NALISHI SIFATIDA (CONFERENCE ON THE ROLE AND IMPORTANCE OF SCIENCE IN THE MODERN WORLD, 2025)
This article discusses the concept of digital tourism, its role in the modern economy, and the prospects for developing the tourism sector in Uzbekistan using digital technologies. It also analyzes the role of online platforms, mobile applications, and artificial intelligence in automating travel services.